KAJIAN POTENSI PENINGKATAN PERMUKIMAN DI KAWASAN PESISIR DAMPAK ABRASI DENGAN PEMANFAATAN INDERAJA (Studi kasus : Pantai wisata Binalatung, Kota Tarakan) - Eko Prihartanto; Muhamad Roem (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2016)
The Tarakan island is geographically surrounded by seas has the potential to damage by abrasion. Potential occurring in areas affected by abrasion thus reducing the total land area. Reduced land area has caused difficulties in the development of human space activities in the activity. The coastal area as an area predominantly inhabited by fishermen to settle because it was easy access to the sea. Another advantage of the coastal region has a panoramic coastal give more value from the tourism sector, it is attracting tourists to visit. Tarakan city have coastal of binalatung to tourist attractions as the beach, which is located in the Eastern city of Tarakan. Attraction area is exposed to abrasion so interesting for the case study research done on the impact of the erosion of the settlement. The study was conducted using remote sensing Google Earth, to the extent that it has impacted the analysis of abrasion, and the condition of the settlement around the attraction. Results obtained in the form of reviews the impact of the area exposed to abrasion with increased abrasion settlement that makes the area a tourist area. Keywords : Abrasion, Google Earth, Settlement.